1993
DOI: 10.1063/1.109137
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel registered polymeric Mach–Zehnder intensity modulator array

Abstract: Described here is the first known demonstration of a registered two level guided wave polymeric electro-optic Mach–Zehnder intensity modulator array. The device consists of two complete vertically stacked levels. Both levels were independently poled and operated. There was no measurable optical or electrical cross talk due to a high resistivity thermoset polymer buffers layer employed. Fabrication and performance of the device is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Exploiting the relatively easy processability, advanced multilevel devices that hardly can be designed with inorganic materials have been demonstrated, such as a vertically stacked directional coupler switch by Hikita and coworkers at NTT [194] and a multilevel Mach-Zehnder intensity modulator array by Tumolillo and Ashley [195]. Figure 23 shows the cross section of the multilevel Mach-Zehnder modulator array, consisting of ten distinct spin-coated layers.…”
Section: Eo Modulation and Samplingmentioning
confidence: 98%
“…Exploiting the relatively easy processability, advanced multilevel devices that hardly can be designed with inorganic materials have been demonstrated, such as a vertically stacked directional coupler switch by Hikita and coworkers at NTT [194] and a multilevel Mach-Zehnder intensity modulator array by Tumolillo and Ashley [195]. Figure 23 shows the cross section of the multilevel Mach-Zehnder modulator array, consisting of ten distinct spin-coated layers.…”
Section: Eo Modulation and Samplingmentioning
confidence: 98%
“…Authors reported the synthesis of poly(aryl vinyl ether) based on a two steps synthetic route (Scheme 1) [9]: the first one concerned a fluoroalkylation with BrCF 2 CF 2 Br while the second one dealt with a zinc mediated elimination. [8,15].…”
Section: Introductionmentioning
confidence: 98%
“…Most EO devices are waveguidetype structures because an electric field can be applied to the waveguides effectively and the waveguide structures could play important role in optically integrated circuits. Various kinds of EO device have been investigated using EO polymer and have been demonstrated to show high bandwidth modulation using a traveling-wave electrode [7,8] and vertically integrated modulator [9,10].…”
mentioning
confidence: 99%